Deciphering community-level knowledge of obstetric fistula and determinants: perspectives elucidated by ordinal logistic regression - Limenih, Miteku Andualem; Melesse, Alemakef Wagnew; Baye, Chernet; Shewabere, Beletew; Mekonnen, Eskedar Getie; Hassen, Hamid Yimam; Berhe, Aster; Shiferaw Alemu, Destaye; Chanie, Wagaye Fentahun (Frontiers in Global Women's Health, 2024)
BackgroundObstetric fistula is a significant cause of maternal morbidity in resource-limited settings, where women often suffer due to a lack of prompt access to skilled obstetric services. It is imperative to comprehend and identify the factors that shape community knowledge about obstetric fistula to enhance prevention strategies, enable early detection, and provide support and treatment to affected women. However, there is a substantial gap in the available evidence concerning the level of community knowledge regarding obstetric fistula and its influencing factors within the Ethiopian context.ObjectiveThis study aimed to investigate the level of knowledge regarding obstetric fistula and identify influencing factors within the communities in Gondar, Ethiopia.MethodsA community-based cross-sectional study was conducted among 663 households. Households were selected using a systematic random sampling technique. Descriptive statistics and exact binomial confidence intervals (CIs) were reported. Group comparisons were performed using the Mann–Whitney U-test or the Kruskal–Wallis test. Parameters with p-value ≤ 0.2 in the univariable ordinal regression were selected for the multivariable ordinal regression model. The proportion odds assumption was checked using the parallel lines test. A multivariable proportional ordinal regression analysis was conducted. p-values <5% were considered statistically significant. Data were analyzed using R version 4.3.1.ResultOf the 663 households, 265 (39.9%; 95% CI: 36.2–43.8), 375 (56.6%; 95% CI: 52.7–60.4), and 23 (3.5%; 95% CI: 2.2–5.2) had low-level, medium-level, and high-level knowledge about obstetric fistula, respectively. Self-employment [adjusted odds ratio (AOR): 0.3; 95% CI: 0.2–0.5], unemployment (AOR: 0.4; 95% CI: 0.2–0.8), income $50–$200 USD (AOR: 5.2; 95% CI: 2–16.1), income > $200 USD (AOR: 7.0; 95% CI: 2.6–22.9), distance from a health facility (AOR: 1.7; 95% CI: 1.1–2.7), non-participation in women’s conferences (AOR: 0.7; 95% CI: 0.5–0.9), and having heard of obstetric fistula (AOR: 4.4; 95% CI: 2.8–7.1) showed statistically significant association with the likelihood of having a high level of knowledge regarding obstetric fistula compared to medium or low levels.ConclusionThe study reveals an alarmingly low level of knowledge about obstetric fistula. Higher income and prior awareness were associated with increased knowledge about obstetric fistula, while self-employment, unemployment, and non-participation in women's conferences were liked to decreased knowledge. Enhancing community knowledge requires a holistic strategy involving cooperation from all stakeholders and tackling broader socio-economic disparities.